Florida 4-H Fashion Revue Guide - Geralyn Sachs; Monica Brinkley; Judith R. Butterfield; Heather M. Janney; Becky V. Bennett; S. Amolsch; Sarah T. Hensley; Pamela Phillippe; Muriel Turner; Stacey Ellison; Brenda Williams; Marnie Ward; et al. (EDIS)
This planning guide and project report is appropriate for 4-H youth who take part in the Florida 4-H Clothing and Textiles Project. This publication offers an exploration of science and art through clothing design, engineering, technology, and craftsmanship. It contains fashion revue guidelines, interview and modeling tips, entry forms, and more.